Manual on compliance with an enforcement of multilateral environmental agreements - Bruch, Carl (UNEP NairobiKE, 2006)
Expands upon Guidelines on Compliance with and Enforcement of Multilateral Environmental Agreements (MEAs). Provides specific examples from around the world on how governments, NGOs, the private sector and other institutions have utilised the various approaches set forth in the Guidelines. Also provides more detailed explanations, checklists and additional resources in order to give depth to the specific approaches.